2014
DOI: 10.1089/jamp.2013.1076
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Spacers and Valved Holding Chambers

Abstract: Spacers and valved holding chambers (VHCs) are pressurized metered dose inhaler (pMDI) accessory devices, designed to overcome problems that patients commonly experience when administering aerosol via a pMDI. Spacers were developed in direct response to patient-related issues with pMDI technique, particularly, poor coordination between actuation and inhalation, and local side-effects arising from oropharyngeal deposition. Current clinical guidelines indicate the need for widespread prescription and use of spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
0
28

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 97 publications
3
47
0
28
Order By: Relevance
“…(1) In vitro work suggests that use of a VHC may reduce the impact of poor actuationinhalation coordination, even if the actuation-inhalation is completely mistimed. (2) Clinical studies have shown that use of a contemporary hydrofluoroalkane (HFA) pMDI with a VHC can increase lung deposition and attenuate oropharyngeal and gastrointestinal deposition, compared with delivery of the same formulation via a dry powder inhaler, (3,4) whereas in vitro work indicates that use of a pMDI with VHC can reduce oropharyngeal deposition relative to the pMDI alone.…”
Section: Introductionmentioning
confidence: 99%
“…(1) In vitro work suggests that use of a VHC may reduce the impact of poor actuationinhalation coordination, even if the actuation-inhalation is completely mistimed. (2) Clinical studies have shown that use of a contemporary hydrofluoroalkane (HFA) pMDI with a VHC can increase lung deposition and attenuate oropharyngeal and gastrointestinal deposition, compared with delivery of the same formulation via a dry powder inhaler, (3,4) whereas in vitro work indicates that use of a pMDI with VHC can reduce oropharyngeal deposition relative to the pMDI alone.…”
Section: Introductionmentioning
confidence: 99%
“…6 In vivo studies demonstrated that reduced deposition of chemical in oropharynx and stomach and increased whole lung deposition of chemical by application of spacer. 3 …”
Section: Discussionmentioning
confidence: 99%
“…2 However, MDIs are not without their own issues which include patients' difficulties with their correct, coordinated use; many patients including the very young, confused, intellectually impaired, or those experiencing acute severe breathlessness will be unable to inhale in anything other than tidal breaths. 3 It is some of these issues that spacers are designed to overcome. Is MDI efficacy with spacer is equivalent to MDI without spacer when used for delivery of combination drugs (Fluticasone and salmeterol)?…”
Section: Introductionmentioning
confidence: 99%
“…La herramienta más utilizada para la Algunos autores mencionan la importancia de una correcta coaptación de la máscara, paso que la mayoría de los profesionales de salud incluidos en nuestro estudio menciona al realizar la encuesta (14)(15)(16).…”
Section: I S C U S I ó Nunclassified
“…RESULTADOS: Se incluyeron 71 profesionales. La técnica de aerosolterapia con aerocámara fue MUY BUENA en 15,49% (IC95% 8,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)65), BUENA en 70,42% (IC95% 58,98-79,77) y REGULAR en 14,08% (IC95% 7,83-24,02) profesionales. La mediana de pasos realizados correctamente fue de 5 de 7 pasos.…”
unclassified